Linux For You (with CD & DVD) (Monthly): Vol.9 Issue.05 July'2011 (EFY Enterpries Pvt. Ltd. New Delhi)
Subscription Period- 2011(Jan to Dec)
Keywords: Computer Science/ Information Science/ MCA/ M Tech CSE